1991
DOI: 10.1073/pnas.88.12.5154
|View full text |Cite
|
Sign up to set email alerts
|

Isoenthalpic and isoentropic temperatures and the thermodynamics of protein denaturation.

Abstract: The standard enthalpy or entropy change upon transfer of a small nonpolar molecule from a nonaqueous phase into water at a given temperature is generally different for different solute species. However, if the heat capacity change is independent of temperature, there exists a temperature at which the enthalpy or the entropy change becomes the same for all solute species within a given class. Similarly, the enthalpy or the entropy change of protein denaturation, when extrapolated to high temperature assuming a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 29 publications
7
93
1
Order By: Relevance
“…7,10 To account for this, it is assumed that the solvation of hydrophilic groups contributes to the enthalpy but not to the entropy so that the solvation entropies of proteins and hydrophobic compounds are similar but not the enthalpies. 22 In contradiction to this assumption and not surprisingly, we find a continuous change of the solvation entropy as one goes from hydrophobic to hydrophilic solutes and in all cases the solvation entropy does not strictly vanish.…”
Section: Introductioncontrasting
confidence: 48%
See 2 more Smart Citations
“…7,10 To account for this, it is assumed that the solvation of hydrophilic groups contributes to the enthalpy but not to the entropy so that the solvation entropies of proteins and hydrophobic compounds are similar but not the enthalpies. 22 In contradiction to this assumption and not surprisingly, we find a continuous change of the solvation entropy as one goes from hydrophobic to hydrophilic solutes and in all cases the solvation entropy does not strictly vanish.…”
Section: Introductioncontrasting
confidence: 48%
“…1 we show such a plot for the original set of proteins 6 used in the analysis of Murphy et al 7 (open triangles) including a linear fit to the data. The data in- 22 showed that convergence of some thermodynamic observable, e.g., the entropy of denaturation of a set of proteins or the entropy of dissolution S within a homologous series of compounds, can generally be expected if that observable is linearly dependent on the variable X (e.g., the number of hydrophobic groups in a homologous series of hydrocarbons) which distinguishes the elements of the series,…”
Section: S(t ) = S(tmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems likely that the entropy change for these large-scale hydrophobic plates converges around T s , similar to the behavior observed for the hydration of small hydrophobic solutes and for the folding of proteins. 14,19,20 At this temperature, the driving force for plate association is only enthalpic. The entropic contribution increases as the temperature decreases.…”
Section: Resultsmentioning
confidence: 96%
“…Kharakoz and Sarvazyan (1993) proposed that the compressible behaviour of a native protein is comparable to that of organic solids. However, proteins in compact intermediate states have liquid-like compressible behaviour (Lee, 1991;. The intrinsic core of a molecule at this stage is small but still preserved and more hydrophobic.…”
Section: Conformation and Compressible Properties Of Proteinsmentioning
confidence: 99%